2008
DOI: 10.1001/archpsyc.65.5.542
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-Associated Depression

Abstract: Amyloid-associated depression may define a subtype of depression representing a prodromal manifestation of Alzheimer disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(76 citation statements)
references
References 63 publications
1
69
0
1
Order By: Relevance
“…Earlier [ 11 C]-PiB-PET findings with small sample size also provided evidence that amyloid load is elevated in late-life depressed MCI subjects [8]. CSF levels of Aß42 were concordantly reduced in MCI suffering from late life depression and correlated with cognitive status [26]. Postmortem analyses have indicated a pronounced deposition of amyloid plaques and tangles in the hippocampus, in brain of AD patients with history of major depression, while subjects with concurrent depressive symptoms at diagnosis of AD exhibited even higher neuropathological changes [27, 28].…”
Section: Discussionmentioning
confidence: 98%
“…Earlier [ 11 C]-PiB-PET findings with small sample size also provided evidence that amyloid load is elevated in late-life depressed MCI subjects [8]. CSF levels of Aß42 were concordantly reduced in MCI suffering from late life depression and correlated with cognitive status [26]. Postmortem analyses have indicated a pronounced deposition of amyloid plaques and tangles in the hippocampus, in brain of AD patients with history of major depression, while subjects with concurrent depressive symptoms at diagnosis of AD exhibited even higher neuropathological changes [27, 28].…”
Section: Discussionmentioning
confidence: 98%
“…Two cross-sectional studies reported an elevation of plasma Aβ42 in individuals with late-life major depression (25) or depressive symptoms and signs compared to non- depressed subjects (26). However, other cross-sectional studies found an inverse relationship between plasma Aβ42 and depressive symptomatology (27) (28) (29). Depression with high plasma Aβ40/Aβ42 ratio was accompanied by impairment in memory, visuospatial task performance, and executive function (29).…”
Section: Plasma and Csf Amyloid Studiesmentioning
confidence: 94%
“…According to some authors, the presence of depressive symptoms associated with a high Aβ40/Aβ42 ratio would represent a prodromal manifestation of AD [20]. However, other hypotheses could be suggested, such as the existence of a primarily ‘amyloid-associated' mood disorder (characterized by Aβ disturbances unrelated to prodromal AD) with resistance to treatment and risk for cognitive decline [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…However, a few data are available regarding the relationship between depression and peripheral levels of Aβ peptides. Higher levels of Aβ40, lower levels of Aβ42, and a greater Aβ40/Aβ42 ratio have been reported in elderly patients with depression, as compared with healthy control subjects [18,19,20]. Moreover, the study by Sun et al [20] highlighted how the so-called ‘amyloid-associated' depression (with high Aβ40/Aβ42 ratio) is characterized by a more severe deficit in memory, visual-spatial skills, and executive functions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation